WHAT MAKES WOMEN WOMENpPRENEUR? - Widya Ardini Prasetya; Noormalita Primandaru; Olivia Barcelona Nasution (UNIVERSITAS PGRI MADIUN, 2024)
This research aims to explain the factors that influence women to become womenpreneurs. The type of research applied in this research is explanatory research by testing the hypothesis that has been formulated. Data is collected through surveys. The sampling technique used in this research was purposive sampling. The hypothesis was tested using multiple regression analysis using IBM SPSS version 22. Financial well-being, self-efficiency, the desire to be independent have a positive and significant effect on interest in becoming a womanpreneur. interest in becoming a womanpreneur, although the need for achievement does not have a significant effect on interest in becoming a womanpreneur. This research only uses female female respondents, for further research you can use female respondents with a more diverse status and also add other variables as antecedents of interest in becoming a womenpreneur. This research can be a reference in looking at the phenomenon of womenpreneurs in the fields of economics, business and entrepreneurship in particular.